El poema «Testamento» de Valle-Inclán: una historia textual, con su primer testimonio impreso - de Juan Bolufer, Amparo (El Colegio de México, 2020)
This paper studies the textual history of the poem “Testamento” by Valle-Inclán. It presents a list of the printed and hand-written evidence of the direct tradition of the text and it edits the first (previously unknown) printed version of the poem. It is concluded that the autographs of the poem as well as the posthumous versions are in fact copies of rough drafts and not definitive texts. This indicates the existence of two separte stages in the writing of the poem, the dating of which this paper attempts to establish. Arguments are put forward to suggest that diverse alterations due are to manipulation on the part of the editors.